2009
DOI: 10.1007/s11244-009-9398-7
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Aged Commercial Three-Way Catalytic Converters

Abstract: The present work demonstrates for the first time that rejuvenation of the catalytic activity of full-scale aged commercial three-way catalytic (TWC) converters is feasible after treatment with weak oxalic acid solution (0.1 M). Up to 50% reduction in CO, 75% in NO x and 32% in HC emissions was attained under warm engine driving conditions following regeneration of three aged TWC converters with 42,500, 156,000 and 165,000 km mileage. Efforts to expand the durability of aged commercial TWC converters installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The increase in the BET surface area after washing was attributed to the uncovering of the pores and it was found that oxalic acid was more effective than citric acid [10]. The uncovering of pores results in regaining catalytic activity due to exposing more active sites that are responsible for CO and NO conversions [35,36]. It appears that the EDDS washing method fails to retrieve the large surface area and pore volume loss (around 50% loss) obtained after aging under real driving conditions and is probably the result of severe thermal sintering as reported [37].…”
Section: Bet Surface Area Measurementsmentioning
confidence: 99%
“…The increase in the BET surface area after washing was attributed to the uncovering of the pores and it was found that oxalic acid was more effective than citric acid [10]. The uncovering of pores results in regaining catalytic activity due to exposing more active sites that are responsible for CO and NO conversions [35,36]. It appears that the EDDS washing method fails to retrieve the large surface area and pore volume loss (around 50% loss) obtained after aging under real driving conditions and is probably the result of severe thermal sintering as reported [37].…”
Section: Bet Surface Area Measurementsmentioning
confidence: 99%